Immunotherapy with corticosteroids in anti-neural autoantibody-associated cognitive impairment: Retrospective case series - Hansen, Niels; Hirschel, Sina; Rentzsch, Kristin; Wiltfang, Jens; Malchow, Berend; Fitzner, Dirk (Frontiers in Aging Neuroscience, 2022)
Background Anti-neural autoantibody-associated cognitive impairment is an increasing phenomenon in memory clinics deserving more attention to applying immunotherapy such as methylprednisolone to improve cognition. Our study aims to investigate the usefulness of intravenous high-dosage corticosteroids in a small cohort of patients suffering from anti-neural autoantibody-associated cognitive impairment. Materials and methods We included in our retrospective case series seven patients presenting diverse neural autoantibodies and cognitive impairments varying from a mild impairment to dementia. We conducted neuropsychological and psychopathological investigations before and after the application of high intravenous methylprednisolone therapy over a 6-month period. Neuropsychological function was assessed by the CERAD (Consortium to Establish a Registry for Alzheimer’s Disease) test battery. Patients were also characterized by assessing their patient files for demographic and clinical data. Results The patients’ cognitive subdomains did not improve according to CERAD in their z-scores before and after immunotherapy. We noted a non-significant trend toward an improvement in semantic fluency and verbal memory consolidation. Patients did not do worse in 4 of 12 (33%) cognitive subdomains in the CERAD test battery. Furthermore, mood dysfunction lessened as a non-significant trend in specific psychopathological features such as reduced affective symptoms, loss of drive, and ruminations. Affective symptoms, loss of drive and ruminations were reduced by 43% after immunotherapy. Discussion Our small pilot study revealed no relevant alleviation of cognitive dysfunction in patients with neural autoantibodies. However, mood dysfunction became less obvious in specific functions concerning affect, drive, and rumination. However, we do not know whether methylprednisolone affects mood dysfunction, as some patients were taking antidepressant drugs at the same time. Our results might indicate that methylprednisolone immunotherapy is associated with impeding the progression of cognitive dysfunction and reducing mood dysfunction. Further large-scale, placebo-controlled studies in a more homogeneous patient population presenting a uniform pattern of neural autoantibodies should be undertaken.